Uncovering the failure of Agile framework implementation using SSM-based action research - Suryaatmaja, Kevin; Wibisono, Dermawan; Ghazali, Achmad; Fitriati, Rachma (Palgrave communications, 2020)
It is undeniable that the Agile software development (SD) framework has been commonly used in information technology projects. However, many of the early adopters failed to implement it properly. Some researchers had proposed a solution by using the adaptation framework as a support, but they cannot clearly explain its development. Furthermore, the correlation between adaptation framework and problem solving is dubious. This study reviews and discusses the literature and empirical studies on the failure of Agile SD implementation by revisiting the supporting framework that used to comprehend the issues in Agile SD implementation. A comparative approach is used to review the literature available in academic databases, such as ProQuest, EBSCO, IEEE, and Scopus, to ensure research originality and novelty. By filtering 87 papers that met the initial criteria, only 4 researchers focused on the area of knowledge management and used the learning process as a supporting framework in Agile SD implementation. However, they did not clearly explain the development of the framework for Agile SD. The author’s initial research on a corporation reveals the failure of Agile SD implementation. Soft systems methodology (SSM)-based action research (AR) proposed to identify the real issues in Agile SD implementation. SSM-based AR provides a solution by clarifying the development of a framework using tacit and explicit knowledge to validate the development process. This study can help practitioners and academics understand the process of Agile SD implementation by early adopters who still need assistance with its application. This study is the first to explore Agile SD implementation in a corporation using the experience-based approach, contributing to knowledge improvement. It contributes to the scholarly literature by presenting concepts that combine human-centric aspects and knowledge management to improve the learning in the organization.